Changes in admission thresholds in English emergency departments. Issue 12 (12th September 2017) - Wyatt, Steven; Child, Kieran; Hood, Andrew; Cooke, Matthew; Mohammed, Mohammed A
Abstract : Background: The most common route to a hospital bed in an emergency is via an Emergency Department (ED). Many recent initiatives and interventions have the objective of reducing the number of unnecessary emergency admissions. We aimed to assess whether ED admission thresholds had changed over time taking account of the casemix of patients arriving at ED. Methods: We conducted a retrospective cross-sectional analysis of more than 20 million attendances at 47 consultant-led EDs in England between April 2010 and March 2015. We used mixed-effects logistic regression to estimate the odds of a patient being admitted to hospital and the impact of a range of potential explanatory variables. Models were developed and validated for four attendance subgroups: ambulance-conveyed children, walk-in children, ambulance-conveyed adults and walk-in adults. Results: 23.8% of attendances were for children aged under 18 years, 49.7% were female and 30.0% were conveyed by ambulance. The number of ED attendances increased by 1.8% per annum between April 2010–March 2011 (year 1) and April 2014–March 2015 (year 5). The proportion of these attendances that were admitted to hospital changed negligiblybetween year 1 (27.0%) and year 5 (27.5%). However, after adjusting for patient and attendance characteristics, the odds of admission over the 5-year period had reduced by 15.2% (95% CI 13.4% to 17.0%) for ambulance-conveyed children, 22.6% (95% CI 21.7% to 23.5%) for walk-in children, 20.9% (95% CI 20.4% to 21.5%) for ambulance conveyed adults and 22.9% (95% CI 22.4% to 23.5%) for walk-in adults. Conclusions: The casemix-adjusted odds of admission via ED to NHS hospitals in England have decreased since April 2010. EDs are admitting a similar proportion of patients to hospital despite increases in the complexity and acuity of presenting patients. Without these threshold changes, the number of emergency admissions would have been 11.9% higher than was the case in year 5.